PENGARUH INDUKSI DAN ZAT PENGATUR TUMBUH TERHADAP PERTUMBUHAN STEK PUCUK KAYU PUTIH (MELALEUCA CAJUPUTI) - Tetty Sriwahyuni (Fakultas Kehutanan Universitas Winaya Mukti, 2018)
The cutting shoot is one of fast growing Malalueca cajuputi seedling. The cutting shoot used from plantation and cajuputi seeds in induction shed. Then, to fast root induction on the cutting shoot must be special treatment is giving hormone from outside. Giving hormonal in Perum Perhutani by IBA (Indole Butyric Acid), but IBA is one of hazard and toxic substances (B3) and not eco-friendly. The object of studies to prove the induction effect on the growth of cajuputi cuttings shoot, the influence of IBA hormone and natural hormone extract of onion to growth of cajuputi cuttings shoot, and determine the best of hormone to growth of cajuputi cutting shoot. Data collected by measuring height of the cajuputi cuttings shoot from the base of stem which has been marked up to the tip of shoots. The measurement of height of cajuputi cutting shoot was repeated 6 (six) times for 90 days so that measurement was done every 15 days. Besides that, there is addition of leaf number since cuttings planted up to 90 HST and root appearance at each treatment. The result of research IBA gives the best growth effect for shoots from Induction that is the highest height compared with other hormones. So this study recommended using shoots of induction with IBA hormone to best growth and eco-friendly.